Surgical Clinic Hospital "Dos de Mayo" - Gastañeta, Guillermo (1922)
Inaugural lecture of the course of 1922 Surgical Clinic of "Dos de Mayo" Hospital by Professor Guillermo Gastañeta, Dean of the Faculty of Medicine of Lima and Professor of Clinical Surgery.